Overlapping Transmission Networks of Early Syphilis and/or Newly HIV Diagnosed Gay, Bisexual and Other Men Who Have Sex with Men (MSM): Opportunities for Optimizing Public Health Interventions - Jennings, Jacky M.; Tilchin, Carla; Meza, Benjamin; Schumacher, Christina; Fields, Errol; Latkin, Carl; Rompalo, Anne; Greenbaum, Adena; Ghanem, Khalil G. (AIDS and behavior, 2020)
Syphilis and HIV among gay, bisexual and other men who have sex with men (MSM) are syndemic suggesting current prevention strategies are not effective. Sex partner meeting places and their networks may yield effective and optimal interventions. From 2009 to 2017, 57 unique venues were reported by > 1 MSM and 7.0% (n = 4), 21.1% (n = 12) and 71.9% (n = 41) were classified as syphilis, HIV or co-diagnosed venues, respectively. Forty-nine venues were connected in one main network component with four online, co-diagnosis venues representing 51.6% of reports and the highest degree and eigenvector centralities. In a sub-analysis during a local syphilis epidemic, the proportion of venues connected in the main component increased 38.7% (61.5% to 86.4%); suggesting increasing overlap in syphilis and HIV transmission and density of the venue network structure over time. This network analysis may identify the optimal set of venues for tailored interventions. It also suggests increasing difficulty of interrupting network transmission through fragmentation.